Pengaruh Kualitas Bahan Tenderloin Meat dan Olahannya Terhadap Kepuasan Tamu di Lorin Hotel Solo - Diah Rizki Aulia; Denny Asmara; Suraji Suraji (Sekolah Tinggi Pariwisata Sahid Surakarta, 2019)
This study was conducted with the aim of knowing the effect of the quality of tenderloin meat ingredients and their preparations on guest satisfaction at Lorin Solo Hotel. There is also a research method used to analyze the data, namely the qualitative method. The author conducted research during On The Job Training in the banquet section through observation, questionnaires and documentation by comparing the theory given with the practice. The population and samples of this research are executive chef, Chef de Partie, Cook, Restaurant Manager, Food and Beverage Service Manager, Service Staff, and Guest of Lorin Solo Hotel. To get optimal and real results, a case study approach is carried out which intends to describe and describe the effect of the quality of the tenderloin meat ingredients and their preparations on guest satisfaction in terms of taste, portion and price. Based on the research results, it is known that: (a) the quality of the tenderloin meat, (b) the quality of the freshness of the meat, (c) the processing of the meat so that it can affect the quality of the product and will also affect guest satisfaction.